Economic reform in Europe and the former Soviet Union: implications for international food markets - Tyers, Rodney (International Food Policy Research Institute, 1994)
Policy reforms in the wake of the Uruguay Round of the General Agreement on Tariffs and Trade (GATT) are expected to reduce food exports in Western Europe. Will the transition to market- oriented policy regimes in Eastern Europe and the former Soviet Union expand agricultural production there, eventually offsetting the reductions in Western Europe and leading to food surpluses for the region as a whole? What effects will these changes have on the rural sectors of developing countries? Addressing these questions quantitatively, Rod Tyers concludes that agricultural exports in Eastern Europe and the former Soviet Union countries could expand enough to more than offset decreases in exports from reforms in Western Europe. Tyers estimates that the combined grain exports of Europe and the former Soviet Union could increase world supplies by as much as 44 million metric tons by 2000, leading to a reduction in world food prices.